Imagens do livro didático de geografia: representações do espaço geográfico - Almeida, Renata Maria de (2013)
This paper aims to discuss the images of the didactic book as a methodology for teaching the category of geographical space. We investigated the third volume of the collection Território e Sociedade no mundo globalizado of the authors Anselmo Lazaro Branco, Claudio Mendonça and Elian Alabi Lucci, used by the students of the Terceiro Ano do Ensino Médio in Colégio Estadual Arnaldo Busato, in the city of Coronel Vivida - PR. In the development of this research, was started a theoretical discussion about the major categories of Geography; working with the image looking for its approximation with approaches to language developed by Mikhail Bakhtin, bringing to the research context, terms such as signs, meaning, speech, sense; held a reading of the Edital do Guia do PNLD (2012) aiming to the verification about the requirements which must be submitted to the illustrations in the didactic book, and was presented an approach about the progress in graphical structuring of educational textbooks. As part of the compositional search results, images of the didactic work were underwent by an analysis, aiming to investigate the possibilities offered for the representation of the geographic space, whereas the images are quite impressive in their variety (cartoons, maps, photographs, paintings, engravings, tables, graphs), however, are poorly worked in didactic compendium. Was also used the data collection through qualitative research, conducted through questionnaires submitted by students and teachers concerning the different views on the illustrations of the work and the representation of space. Through the results presented in this research, it is expected to contribute to better use of the image as language, listing its importance for the understanding of geographic knowledge.